Optimizing Practitioner Lecturers in Independent Learning: A Case Study of MBKM Implementation at Muhammadiyah University of Maumere - Sunardin Sunardin; Erna Yayuk; Agus Tinus (STAI Hubbulwathan Duri, 2025)
The Independent Learning–Independent Campus (MBKM) policy aims to bridge academic knowledge with practical industry skills. However, its implementation in private or regional universities, such as Muhammadiyah University of Maumere, remains underexplored. One key element for success—practitioner lecturers—requires deeper investigation in this context. This qualitative case study examines the role of practitioner lecturers in supporting independent learning under the MBKM framework. Data were collected through in-depth interviews with program heads, 24 practitioner lecturers, and 624 students, supported by document analysis and participatory observation. Data analysis followed Miles and Huberman’s model, emphasizing reduction, display, and conclusion drawing. The study finds that practitioner lecturers significantly contribute to bridging theoretical content with real-world practice, enhancing student engagement and skill acquisition. Their industry experience provides students with relevant insights aligned with local and national workforce demands. However, time constraints, lack of pedagogical training, and limited alignment between academic and industrial expectations emerged as major challenges. Despite institutional support, the effectiveness of practitioner lecturers is hindered by structural and operational barriers. Students also report difficulty adapting to practice-oriented teaching styles without sufficient theoretical grounding. Optimizing practitioner lecturers in regional MBKM implementation requires targeted training, flexible scheduling, and improved coordination with industry partners. This study offers practical recommendations for enhancing independent learning outcomes through strategic lecturer engagement in similar higher education settings.